Circulating inflammatory cells in patients with metastatic breast cancer: Implications for treatment - Gianni, Caterina; Palleschi, Michela; Schepisi, Giuseppe; Casadei, Chiara; Bleve, Sara; Merloni, Filippo; Sirico, Marianna; Sarti, Samanta; Cecconetto, Lorenzo; Di Menna, Giandomenico; Schettini, Francesco; De Giorgi, Ugo (Frontiers in Oncology, 2022)
Adaptive and innate immune cells play a crucial role as regulators of cancer development. Inflammatory cells in blood flow seem to be involved in pro-tumor activities and contribute to breast cancer progression. Circulating lymphocyte ratios such as the platelet-lymphocytes ratio (PLR), the monocyte-lymphocyte ratio (MLR) and the neutrophil-lymphocyte ratio (NLR) are new reproducible, routinely feasible and cheap biomarkers of immune response. These indexes have been correlated to prognosis in many solid tumors and there is growing evidence on their clinical applicability as independent prognostic markers also for breast cancer. In this review we give an overview of the possible value of lymphocytic indexes in advanced breast cancer prognosis and prediction of outcome. Furthermore, targeting the immune system appear to be a promising therapeutic strategy for breast cancer, especially macrophage-targeted therapies. Herein we present an overview of the ongoing clinical trials testing systemic inflammatory cells as therapeutic targets in breast cancer.